Seeking new approach for therapeutic treatment of cholera disease via inhibition of bacterial carbonic anhydrases: experimental and theoretical studies for sixteen benzenesulfonamide derivatives - Rosaria Gitto; Laura De Luca; Francesca Mancuso; Sonia Del Prete; Daniela Vullo; Claudiu T. Supuran; Clemente Capasso (Taylor & Francis Group, 2019)
A series of sixteen benzenesulfonamide derivatives has been synthesised and tested as inhibitors of Vibrio cholerae carbonic anhydrase (CA) enzymes, belonging to α-CA, β-CA, and γ-CA classes (VchCAα, VchCAβ, and VchCAγ). The determined Ki values were compared to those of selected human CA isoforms (hCA I and hCA II). Structure-affinity relationship analysis highlighted that all tested compounds proved to be active inhibitors of VchCAα at nanomolar concentration. The VchCAβ activity was lower to respect inhibitory efficacy toward VchCAα, whereas, these benzenesulfonamide derivatives failed to inhibit VchCAγ. Interestingly, compound 7e combined the best activity toward VchCAα and VchCAβ. In order to obtain a model for binding mode of our inhibitors toward bacterial CAs, we carried out docking simulations by using the available crystal structures of VchCAβ.